Optimization of Integrated Logistic Support in the Natuna Region to Support Kogabwilhan I Operations - Teguh Trilaksana; Andi Mawanto (Jurnal Perikanan dan Kelautan, 2022)
This study analyzes the effect of integrated logistical support in the Natuna region to support the operational readiness of Kogabwilhan I, further optimizing integrated logistics support in the Natuna region to support the success of operations carried out by Kogabwilhan I. Based on data processing, the research results show that there is a positive and significant effect of integrated logistics support in the Natuna region on the operational readiness of Kogabwilhan I, so it can be said that the higher the integrated logistics support in the Natuna region, the higher the operational readiness of Kogabwihan I. By completing the DSP of the anchoring facility monitoring organization and competent debriefing support in the field of logistics and carrying out improvements to facilities and infrastructure that are not yet optimal or those that do not yet exist based on the standardization book of Indonesian Navy bases, it can support the successful operation of Kogabwilhan I.